An Evaluation of Solar Photovoltaic System Depreciation Using PVSOL - Shweta Baviskar,; Gaurav B. Patil,; Yash Patil,; Yogita Solanki,; Sandeep Ushkewar, (International Journal of Engineering and Management Research, 2024)
This study provides a thorough examination of the design approaches for solar photovoltaic (PV) systems, utilizing the PVSOL software. Given the growing need for renewable energy sources, it is crucial to optimize solar PV installations. An in-depth analysis was conducted to determine the factors that influence the system's performance. These factors include the geographical location, shading effects, and module configurations. PVSOL is used to conduct a thorough analysis of these elements in order to assess their influence on the system's efficiency and amount of energy it produces. The study incorporates both theoretical analysis and practical simulations to offer significant insights into the design process. The results highlight the importance of meticulous design considerations in optimizing energy generation and system performance. This research enhances the development of solar PV technology by providing valuable information on the most effective ways to design optimal systems. This, in turn, helps to promote the shift towards sustainable energy alternatives.